The Role of Vitamin D Deficiency in African American Women with Systemic Lupus Erythematosus (SLE) - Zuljevic, Matea; Ensan, Donna; Handulle, Imaan (Université d'Ottawa | University of Ottawa, 2016)
Background: Systemic lupus erythematosus (SLE) is a multi-organ, autoimmune disease that is mainly characterized by the overproduction of antibodies attaching to the nucleus of the cell and marking it for destruction. Overtime, this autoimmune response leads to an array of clinical manifestations by causing blood vessels to expand and leak fluid, resulting in swelling and inflammation of several parts of the body. The reported prevalence of SLE worldwide is 20 to 150 cases per 100,000, mostly affecting African American women, specifically those of childbearing age (20 to 40 years). Although SLE is a multifactorial disease, studies suggest a strong association between its progression and vitamin D deficiency. Objective: To investigate the role of vitamin D deficiency in disease activity of SLE among African American women. Methods: A structured literature review was conducted using PubMed, Google Scholar, and Lancet databases. An effective search strategy was developed to filter all appropriate and relevant studies on the effects of vitamin D deficiency in African American women with SLE. The inclusion criteria were vitamin D deficiency, systemic lupus erythematosus, African American, and women.  The articles selected were peer-reviewed journals, published after 2000, and written in the English language. After several search parameters were conducted, six out of 42 articles remained and were used to support this study. Results: The selected scientific articles show that African American women affected by SLE have insufficient levels of 25-hydroxyvitamin D [25(OH)D]. This deficiency increases the severity of SLE and explains the abnormalities experienced by many patients with this disease. Conclusion: All of the articles reviewed suggest that vitamin D deficiency is associated with the progression of SLE in African American women.